2018
DOI: 10.1080/19942060.2018.1526119
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane growth prediction based on meteorological parameters using extreme learning machine and artificial neural network

Abstract: Management strategies for sustainable sugarcane production need to deal with the increasing complexity and variability of the whole sugar system. Moreover, they need to accommodate the multiple goals of different industry sectors and the wider community. Traditional disciplinary approaches are unable to provide integrated management solutions, and an approach based on whole systems analysis is essential to bring about beneficial change to industry and the community. The application of this approach to water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…described how ML techniques could efficiently model complex hydrological systems such as floods. Many ML algorithms, e.g., artificial neural networks (ANNs) [44], neuro-fuzzy [45,46], support vector machine (SVM) [47], and support vector regression (SVR) [48,49], were reported as effective for both short-term and long-term flood forecast. In addition, it was shown that the performance of ML could be improved through hybridization with other ML methods, soft computing techniques, numerical simulations, and/or physical models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…described how ML techniques could efficiently model complex hydrological systems such as floods. Many ML algorithms, e.g., artificial neural networks (ANNs) [44], neuro-fuzzy [45,46], support vector machine (SVM) [47], and support vector regression (SVR) [48,49], were reported as effective for both short-term and long-term flood forecast. In addition, it was shown that the performance of ML could be improved through hybridization with other ML methods, soft computing techniques, numerical simulations, and/or physical models.…”
mentioning
confidence: 99%
“…Such applications provided more robust and efficient models that can effectively learn complex flood systems in an adaptive manner. Although the literature includes numerous evaluation performance analyses of individual ML models [49][50][51][52], there is no definite conclusion reported with regards to which models function better in certain applications.In fact, the literature includes only a limited number of surveys on specific ML methods in specific hydrology fields [53][54][55]. Consequently, there is a research gap for a comprehensive literature review in the general applications of ML in all flood resource variables from the perspective of ML modeling and data-driven prediction systems.Nonetheless, ML algorithms have important characteristics that need to be carefully taken into consideration.…”
mentioning
confidence: 99%
“…Integrated approaches based on complex systems for forecasting the growth of sugarcane based on meteorological parameters using extreme machine learning and neural networks were able to show a more generalized model of forecasting for the growth of sugarcane, bringing benefits to industry and the community [52].…”
Section: Discussionmentioning
confidence: 99%
“…The market development of various solar thermal collectors was studied and compared with PV solar farms (Kramer & Helmers, 2013). To avoid time-consuming and also expensive experimental examinations in the PV/T systems, soft machine-based forecasting methods are developed (Chau, 2017;Chuntian & Chau, 2002;Fotovatikhah et al, 2018;Hajikhodaverdikhan, Nazari, Mohsenizadeh, Shamshirband, & Chau, 2018;Taherei Ghazvinei et al, 2018;Wu & Chau, 2011). These models can forecast the output efficiently based on some required input data.…”
Section: Introductionmentioning
confidence: 99%